Outcome of Very Premature Newborn Receiving an Early Second Dose of Surfactant for Persistent Respiratory Distress Syndrome - Greiner, Eva; Wittwer, Apolline; Albuisson, Eliane; Hascoët, Jean-Michel (Frontiers in Pediatrics, 2021)
Background: Infants presenting respiratory distress syndrome (RDS) not responding to surfactant often receive a second instillation. Few studies evaluated the consequences of this second administration. This study aimed at determining the outcome of infants presenting persistent RDS and receiving an early second dose of surfactant. Methods: Infants below 32 weeks' gestation who received a second dose of 100mg/kg of surfactant within the first 72 h of life, were retrospectively involved in this 42 months' study. They were matched to two controls receiving a single dose of 200mg/Kg based upon gender and gestational age. Results: 52/156 infants receiving two doses (Group 2-doses) were significantly more often SGA [22 (42%) vs. 21 (20%) p = 0.04] and outborn [29 (56%) vs. 13 (12%) p = 0.001]. They had received antenatal corticos teroid therapy less often [26 (50%) vs. 89 (86%) p = 0.001] and presented more severe RDS based upon FiO2 level, oxygenation index and radiography. Group 2-doses survival was lower (65.4% vs. 79.6 % p < 0.1) but surviving infants did not have different morbidity than controls. Discussion: Premature newborn receiving a second dose of surfactant had adverse antenatal characteristics, presented more severe RDS and only partially responded to the first dose. Outcomes of surviving infants who received 2 doses of surfactant were comparable to others.